2000
DOI: 10.2500/105065800781602885
|View full text |Cite
|
Sign up to set email alerts
|

Chondromyxoid Fibroma of the Nasal Septum: A Case Report Emphasizing Clinical Correlation

Abstract: Chondromyxoid fibromas are uncommon tumors most often seen in long bones of adolescent and young males. Involvement of craniofacial bones is extremely unusual, with sporadic case reports described in the literature. We describe the first case of chondromyxoid fibroma arising in the nasal septum with local destruction and expansile growth into the ethmoid bone and inferior turbinate in a 60-year-old female. The fortuitous discovery of this otherwise asymptomatic lesion and its follow-up are detailed. The litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 8 publications
0
6
1
Order By: Relevance
“…In contrast, when craniofacial involvement occurs, females of age more than 40 are twice likely to be affected. [5] Our case slightly contradicts these trends as our patient was only four years old.…”
Section: P R O V I S I O N a L L Y A C C E P T E D F O R P U B L I C A T I O Ncontrasting
confidence: 53%
See 1 more Smart Citation
“…In contrast, when craniofacial involvement occurs, females of age more than 40 are twice likely to be affected. [5] Our case slightly contradicts these trends as our patient was only four years old.…”
Section: P R O V I S I O N a L L Y A C C E P T E D F O R P U B L I C A T I O Ncontrasting
confidence: 53%
“…Craniofacial involvement is quite rare, approximately 5.4% with mandible and maxilla most commonly affected. [5] Within the head and neck area, some cases have been discovered in paranasal sinuses, clivus, sella turcica and mastoid process. [6] According to Nazeer T et al the nasal cavity in chondromyxoid fibroma is infrequently involved; this…”
Section: Discussionmentioning
confidence: 99%
“…Scattered bizarre cells with pleomorphic nuclei are not unusual and may be suggestive of chondrosarcoma. 2,7,11,14,15 Cytogenetics Cytogenetic studies of CMF have reported that most clonal abnormalities affect chromosome 6, especially rearrangement of the long arm of this chromosome. This may be due to the fact that chromosome 6 is location for several genes responsible for normal development of cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only 4 cases of CMF involving the nasal septum have been reported. 2,5,6,7 Here we report a fifth case located in the nasal septum, in a 24-year-old man. The tumor was removed via endoscopic resection.…”
mentioning
confidence: 85%